2018
DOI: 10.1038/s41430-018-0285-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and increased food insecurity are associated with adverse body composition changes among pregnant and lactating Kenyan women

Abstract: HIV infection was associated with lower weight, fat mass, fat-free mass, TSF, AFA, and MUAC values during pregnancy and lactation, while food insecurity was intermittently associated with body composition. This suggests that pregnant and lactating women living with HIV and food insecurity could benefit from nutritional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…The Latin American and Caribbean Scale (ELCSA) was used in Mexico to investigate the relationship between FI and hearing disorders at birth. Two studies [38,39] (5.4%) used the 9-item individually focused food insecurity access scale (IFIAS) that was validated in 2015 in Uganda in a survey of pregnant women [40]. The remaining studies used individual questions to assess FI (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Latin American and Caribbean Scale (ELCSA) was used in Mexico to investigate the relationship between FI and hearing disorders at birth. Two studies [38,39] (5.4%) used the 9-item individually focused food insecurity access scale (IFIAS) that was validated in 2015 in Uganda in a survey of pregnant women [40]. The remaining studies used individual questions to assess FI (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the way to evaluate FI, some studies (n = 6, 16.3%) considered FI a continuous variable and used mean scores for analysis [13,24,36,38,39,41]. In the others it was considered as a categorical or ordinal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most outstanding applications of bioimpedance in healthcare is the estimation of body composition, which is normally applied to assess the nutritional and hydration status and useful in multiple clinical areas: obstetrics [13], postoperative monitoring [14], critical care [15], pregnancy and lactation [16], gastroenterology [17], nutrition [18], chronic inflammation [19], obesity [20], or sports science [21]. An area of great interest is nephrology since it has been shown that bioimpedance methods can help in the dialysis process to achieve the desired euvolemic state [12].…”
Section: Introductionmentioning
confidence: 99%